School Anxiety in Children and Adolescents with Chronic Pain - K. E. Jastrowski Mano (Pain Research and Management)
Anxiety is highly prevalent in pediatric chronic pain. This comorbidity has been explained by the presence of shared mechanisms underlying the development and maintenance of chronic pain and anxiety. Accumulating evidence demonstrates that school is a significant source of anxiety among youth with chronic pain and that anxiety contributes to school-related functional impairment in this population. This article reviews the cooccurrence of pediatric chronic pain and anxiety, identifies unique sources of heightened school anxiety among youth with chronic pain, and describes current approaches for assessing anxiety in pediatric pain settings. Highlighted by this review is the absence of a comprehensive evidence-based approach for assessing school anxiety in pediatric chronic pain. Given the psychometric limitations inherent to gathering data from a single source, recommendations for advancing measurement methods are provided. Novel approaches may be needed to shed more light on the way in which school anxiety is experienced in pediatric chronic pain.